Exploring the Influence of STARA Awareness on Job Outcomes and Well Being Outcomes among University Level Teachers - Bhattarai, Supuspa; Shukla, Ph.D., Shivam (Devkota Journal of Interdisciplinary Studies, 2025)
The rise of Industry 4.0, driven by STARA (Smart Technology, AI, Robotics, and Algorithms), has transformed business sectors, yet its impact on higher education particularly among teaching faculty in developing contexts like Nepal remains understudied. Grounded in the Job Demands-Resources (JD-R) theory, Career Planning theory and Job Insecurity theory, this study investigates how STARA awareness influences job outcomes (organizational commitment, career satisfaction, turnover intentions) and wellbeing outcomes (depression, cynicism). This study aims to explore the relationship between STARA Awareness on Job Outcomes and Well Being Outcomes. These relationships were assessed using multivariate technique i.e. MANOVA from the responses collected via online and physical contact from 133 university level teachers working in and in different affiliated colleges of Tribhuvan University, Pokhara University, Purbanchal University and others. Using a quantitative survey design, data were analyzed via MANOVA, revealing a significant overall effect of STARA awareness on combined outcomes (p < .05). Follow up ANOVA showed STARA awareness significantly impacted organizational commitment (F = 2.708, p < .01) and depression (F = 2.125, p < .05), but had no significant impact on career satisfaction, turnover intentions, or cynicism. Notably, well being outcomes fully mediated the STARA Awareness and Job Outcomes relationship. Practical implications highlight the need for universities to implement STARA training programs to reduce depression risks and strengthen organizational commitment, while policymakers should address automation anxiety through institutional support. By bridging JD-R theory with the employee mental health discourse, this study offers actionable insights for academia and HR professionals navigating the STARA era.